MENANAMKAN ETIKA DAN TEORI MORAL DALAM PENDIDIKAN KARAKTER: ANALISIS KASUS CYBERBULLYING DI KOTA KUPANG - Stevan Christian Antoin; Jenita Selan; Juan Delgibed Sinlae; Salfa Putra Neno; Riyo Yomiarton Hilly (STKIP Subang, 2026)
This study aims to analyze the application of ethical principles and moral theories in character education as an effort to prevent and address cyberbullying in Kupang City. The growing phenomenon of digital bullying among students requires educational strategies that focus not only on cognitive aspects but also on moral character formation. Using a descriptive qualitative approach, this study examines the relevance of deontological ethics, utilitarianism, virtue ethics, Kohlberg’s moral development theory, and Habermas’s discourse ethics within the framework of character education. The findings reveal that integrating ethical principles into curricula, extracurricular activities, and daily value practices strengthens students’ moral awareness, nurtures empathy, and reduces the tendency to engage in cyberbullying. Furthermore, the involvement of families and communities plays a crucial role in reinforcing the implementation of character education in schools. In conclusion, ethics-based and moral theory–driven education can serve as a fundamental foundation for developing young generations who are intelligent, empathetic, and responsible in the digital era.